Evaluasi Peran DPS dalam Menjamin Kepatuhan Syariah pada Bank Syariah Indonesia (BSI) - Hasmi, Athira Putri; Kamaruddin, Kamaruddin; Possumah, Bayu Taufiq; Majid, Jamaluddin; Wawo, Andi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2025)
This study aims to analyze the role of the Sharia Supervisory Board (DPS) in ensuring compliance with sharia principles and to assess the effectiveness of its implementation at Bank Syariah Indonesia (BSI). The research employs a qualitative method using a library research approach, with BSI as the primary object of study. Data were collected through Google Scholar to obtain various relevant journals and scientific literature that contribute to building a conceptual foundation regarding the functions and effectiveness of the DPS. In addition, this study also utilizes secondary data in the form of BSI’s 2024 Annual Report, which was published on the official BSI website. The findings indicate that the DPS plays a highly strategic role in maintaining and ensuring sharia compliance within BSI. This role is not limited to supervisory functions but also includes providing guidance, advice, evaluations, and considerations in decision-making processes and the development of sharia-compliant banking products. Another significant finding is the existence of multiple positions held by DPS members; however, the number of positions does not exceed the maximum limit of four Islamic financial institutions, thus remaining in accordance with applicable regulations. This indicates that DPS members have performed their duties professionally while adhering to established rules. Nevertheless, this study recommends that DPS members who also serve in other Islamic financial institutions continue to enhance the quality of their supervision and the effectiveness of their performance in order to further strengthen the overall implementation of sharia principles.